The Development of Moral Qualities in Youth Psychology of the Past Days - Toshpulatov Abdulaziz Kuvondik oglu; Karomatov Akbar Abramat oglu (Zien Journals, 2022)
The first example of the Uzbek novel about the influence of the work "Last Days" on the psychology of youth and the formation of moral qualities in the psychology of youth
Keywords: Mind; moral qualities; memory; imagination